Evaluation of The Effect of Spoofing on Dual-Frequency Global Navigation Satellite System (GNSS) - Dinesh Sathyamoorthy; Ahmad Firdaus Ahmad Kazmar; Amirah Sakinah Mohd Rozlan; Mohammad Ghazdly Adril Ghazali; Noor Hazimah Syamila Mat Najib (Journal of Engineering Technology and Applied Physics, 2024)
This paper aims to assess the impact of Global Navigation Satellite System (GNSS) spoofing on the performance of a Garmin GPSMAP 66sr dual-frequency GNSS receiver. The evaluation is conducted through field assessments under three conditions: 1) single-frequency GPS L1 coarse acquisition (C/A) only, 2) single-frequency GPS L1 C/A and Galileo E1 open service (OS), and 3) dual-frequency GPS L1 C/A and L5, as well as Galileo E1 OS and E5a. The results emphasise the critical role of multifrequency GNSS in mitigating spoofing. In the dual-frequency multi-GNSS mode, spoofing does not occur as the GPS L5 and Galileo E5a signals remain unaffected by spoofing signals in the L1 / E1 band. In the single-frequency multi-GNSS mode, the higher number of observed GNSS satellites contributes to higher minimum spoofing power levels and longer durations between position fix loss and spoofing as compared to the GPS only mode.